The Stormbringer - Archita Mishra (India BECOMESHAKESPEARE.COM, 2016)
"Accidents happen. It was an accident that changed thirteen-year old Elijah from an ordinary farmer's boy into an Invisitus, a supreme warrior with unparalleled powers. Or do they? Elijah soon learns that the 'accident' was but the product of a century-old prophecy which predicted that the boy with the blue light, he, would have the fate of his entire race resting in his hands. With the help of the brotherhood, Elijah must learn to harness his powers and grow into his role as the Stormbringer, before the evil Occidierum succeed in destroying him and all the other Invisitae. Join Elijah as he navigates a world brimming with magic, prophecies, deceit and unlikely friendships. After all, the paths of an Invisitus are infinite. "Archita writes with verve, confidence, imagination and feeling that belie her youth. A wonderful debut that promises much more to come." - Dr. Shashi Tharoor, M.P., Lok Sabha & Chairman, Parliamentary Standing Committee on External Affairs "A classic coming of age story. It is a wonderful adventure for those who love epic fantasy, superheroes and magic." - Farah Oomerbhoy, Author, The Avalonia Chronicles"
Keywords: Science Fiction -- Science Fiction; Fantasy -- Fantasy